An Inside-Out Architectural Design Approach to Enhancing Home Nostalgia and Making Residential Spaces a “Sweet Home - El-Gammal, Yasser O.; Abd EL-Mageed, Manar Medhat; EL Kattan, Ahmad Abd El-Monem (Journal of Neonatal Surgery, 2025)
Architects and interior designers worldwide strive to create cozy home environments using design theories, trends, and common knowledge. However, research shows a lack of architectural and design approaches aimed at addressing the persistent nostalgia many feel for their homes.This study examines the link between emotions and home design, focusing on nostalgia. It investigates how certain areas elicit feelings and how these influence home features, aiming to enhance nostalgia through design. Also, examines differences between "Shelter," "House," and "Home," the significance of "Home Sweet Home," and nostalgia linked to places and memories. It presents four design criteria, two case studies, and a discussion on architectural nostalgia. Key topics include which elements create intimacy, the impact of emotions on homes, and tools for designers to cultivate this connection. We distinguishes between "Shelters," "House," and "Home," exploring nostalgia related to places and memories. It concludes with four design parameters, an inside/out design criteria, and guidelines for enhancing home nostalgia. Applying these to a mansion case study, it stresses the importance of collaboration between architects and families to personalize spaces based on nostalgic memories..